The Influence of Variety Seeking, Dissatisfaction, and Lifestyle on Smartphone Brand Switching from Android to iPhone (A Study on Students of UPN "Veteran" Jawa Timur) - Redyvastyo Ari Nurogo; Ety Dwi Susanti (International Journal of Social, Economic, and Business, 2025)
The intense competition in the smartphone industry in Indonesia requires companies to continuously innovate in order to maintain consumer loyalty and prevent brand switching. The phenomenon of brand switching, particularly from Android to iPhone, is influenced by various psychological and social factors. This study aims to analyze the influence of Variety Seeking, Dissatisfaction, and Lifestyle on brand switching among students of UPN "Veteran" Jawa Timur. This research employs a quantitative method with a causal associative design. The sample consists of 100 UPN "Veteran" Jawa Timur students who have switched from Android to iPhone, selected using purposive sampling techniques. Primary data were collected through an online questionnaire and analyzed using multiple linear regression with SPSS software. The findings reveal that the three variables significantly affect brand switching, both collectively (simultaneously) and individually (partially). The adjusted coefficient of determination (Adjusted R Square) shows that these factors collectively explain 40.2% of the variation in brand switching decisions. Further analysis indicates that Variety Seeking is the most dominant factor, contributing 47.38%, followed by Dissatisfaction at 40.24%, and Lifestyle at 12.38%. Based on these results, the desire to seek new experiences emerges as the primary driver of brand switching, strengthened by dissatisfaction with previous products and validated by lifestyle compatibility.